An Antimicrobial Activity of Moringa Oleifera Extract in Comparison to Chlorhexidene Gluconate (In vitro study) - Khulood M Alsaraf; Suha T Abd; Nada S Husain (College of Dentistry/ University of Baghdad, 2016)
Background: Oral diseases persist to be a major health problem all over the world. Various bacteria and fungi are found to be the possible pathogensresponsible for the oral diseases. Moringa oleifera it is an extraordinary nutritious vegetable tree with many different uses. These leaves have high medicinal value. In the present study, antibacterial and antifungal activities of aqueous extracts of plant Moringa oleifera in comparison to chlorohexidene gluconate and deionized water were determined. Materials and methods: The leaves of plant of Moringa oleifera were collected from College of Pharmacy; Baghdad, Iraq. Tested microorganism (bacterial and fungal) was isolated from different clinical specimens. In-vitroantimicrobial activity was performed by agar well diffusion method on Muller Hinton agar medium. Results: The water extract of Moringa oleiferashowed antibacterial effect on the tested organisms: Staphylococcus aureus, Streptococcus spp. and Enterococcus faecalis. Aqueous extract showed maximum zone of inhibition against S.aureus. Conclusion: Moringa olifera can be used as safe and cheap plant antimicrobial agent. Key words: Moringa oleifera, Antimicrobial effect, Chlorohexidene gluconate.